Performance evaluation of mobile sensor communication based on crossbow motes - Amy Amilya, Jamil (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Wireless Sensor Network (WSN) has become an academic research due to its wide range of supported application and usage from military field, area monitoring, air pollution monitoring, and healthcare monitoring. WSN is consists of large number of small sensor nodes. In most existing research study, sensor nodes are assumed to be static nodes. In many application, the sensor nodes are mobile. In this paper, we investigate how the mobile sensor networks perform in the case when the mobile sensors moves with different speed, direction and distance from the base station. We investigate the performance sensor nodes using Berkeley Mica2 sensor nodes when the sensor nodes moves with the speed of 5 ms" and I0 ms'. The mobile Mica2 sensor is attached to the Parallax Boe-Bot robot. Boe-Bot robot is use to assist the movement of the mobile sensor nodes. The mobile sensor nodes will send the packets to the base station node which is connected through USB port to the computer. The mobile sensor nodes starts moving at different location: near to the base station and further from the base station. The packets are calculated while the mobile sensor nodes moves. The performance of mobile sensors are evaluated in term of throughput. The result shows that the number of throughput is increased when the sensor moves with the high speed near to the base station.